Factor influences selection of islamic financial: A study on workers bank preference at building of Setiausaha Kerajaan Negeri Selangor / Muhammad Asyraf Mohd Anuar - Mohd Anuar, Muhammad Asyraf (2016)
Islamic banking system as a new banking structure has drastically increased its operations in order to expand its usage in different part of the world. The development of Islamic banking in the past three decades shows a paradigm shifts in banking institution. The main objective of the study is to explore how much the bank consumers are influenced by the Islamic banking criteria and this research is also to identify the factors that influence customers in preferring Islamic banking services. A structural questionnaire is constructed to collect data to answer the research questions as being framed on related affective factors that influence consumers’ preference towards Islamic banking services among workers at Setiausaha Kerajaan Negeri Selangor building. In this study, we have hypothesis testing and reliability analysis. The results show that religious needs and awareness, services quality, social influence, and profitability has positive impact on Islamic banking services. One potential limitation of this study is the size and composition of the group which participated in the study. Therefore, a generalization about the entire population of Malaysian banking customers of banking sector is inappropriate. This study could not incorporate all levels of diverse factors that might influence consumers’ preference in Islamic banking service. The findings of the study can facilitate the Islamic banking service providers to introduce innovative service offering in according to Islamic Shariah principle